The electro-spun composite nanofibers of PVA/Chitosan/Aloe Vera/Calendula officinalis: fabrication and characterization for wound dressing - Kanchit Kamlangkla; Udomdej Pakdee; Piewpan Prajansri; Chaiwat Phrompet; W Pormsila (Advances in Natural Sciences Nanoscience and Nanotechnology, 2025)
Abstract The work was to investigate the ratio of the composite electro-spun nanofibers between polyvinyl alcohol (PVA)/chitosan (CS)/aloe vera (AV) and Marigold (MG, Calendula officinalis ) (PVA/CS/AV: MG) using tetraethyl orthosilicate (TEOS) a crosslinking agent for wound dressing. The optimal composite nanofiber could be obtained at up to 10% MG concentrations in 1.0% acetic acid. However, a suitable composite for wound dressing fabrication is by blending the PVA/CS/AV and MG with a weight ratio of 90:10. The size of composite nanofibers obtained an average diameter of 129.9 nm, and the tensile strength was 3.5 MPa. The modulus and percentage elongation at break were about 142 and 18.5, respectively. The contact angle between droplets and composite nanofibers was averaged at 41°, presenting the increase of the swelling behavior to 441%. The average steam transmission rate of all ratios was approximately 1.5 g d −1 l −1 , corresponding to the porosity in the fibers for 0.9 μm (91.5%). The composite nanofibers demonstrated significant antibacterial activity, with inhibition radii of 7.3 mm against Staphylococcus aureus and 5.5 mm against Escherichia coli . These findings indicate the potential of the PVA/CS/AV/MG composite nanofiber for advanced wound dressings, promoting wound healing, moisture management, and adequate antibacterial protection.
Keywords: Electrospun Nanofibers in Biomedical Applications; Coconut Research and Applications; Electrohydrodynamics and Fluid Dynamics